(untitled) (Research, Society and Development, 2023)
Cancer can be defined as a set of unpredictable mutations suffered by cells in the body. Three types of malignant neoplasms are mainly responsible for the alarming number of skin cancer cases. The most common and most curable are the Spinocell Carcinoma and Basal Cell Carcinoma, while the most aggressive type and with high rates of metastatic dissemination is called melanoma. The objective of this research is an epidemiological analysis of the years 2015 to 2022, about cutaneous malignant melanoma and other malignant skin neoplasms in all regions of Brazil. The study is descriptive and quantitative, with data collected from the DATASUS online platform. The results showed that the South is the region with the most cases of melanoma and other skin malignancies per 100,000 inhabitants. Another noteworthy result, is the high number of skin cancer diagnoses in the pandemic period, having a reduction of only 24.42% in the peak year of the pandemic, but the cases diagnosed in the pandemic period are still greater than the sum of all diagnoses in the years 2015 through 2018. Therefore, we conclude that the large number of diagnosed cases of skin cancer is due to awareness campaigns, access to specialists, and the implementation of an effective online database. However, melanoma diagnoses in stage 4 are alarming and require measures to promote diagnosis at early stages of the disease.